Keefektifan Permainan Tradisional Engklek terhadap Keaktifan Belajar PPKn Siswa Kelas III SD Negeri 1 Karangmulyo Kendal - Nissa, Alvy Khoirun; Agustini, Ferina; Kiswoyo, Kiswoyo (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2019)
The aim of this research is to find out the effectiveness of traditional games â€œengklekâ€ in the liveliness studying of PPKn third grade students of SD N 1 Karangmulyo Kendal. The type of this research is experimental research in the form of Pre-Experimental Design, because there is no control variable, and the sample is not randomly selected. Pre-Experimental Design that used is One Group Pretest-Post Test Design. The study population was third grade students of SD N 1 Karangmulyo Kendal which will be used as the experimental class. The samples taken in this study were all third grade students of SD N 1 Karangmulyo Kendal consisting of 10 males and 10 females to be sampled using Saturated Sampling techniques. The data of this research were obtained through interviews, observations with the pretest post test, and documentation. Based on the results of the analysis the data tested was obtained = 11,723. Then consulted with a table with db = (+) - 2 = (20 + 20) - 2 = 38 and a significance level of 5% is known = 2.021 so> that is 11.723> 2.021. Thus H0 is rejected and Ha is accepted. This means that there are differences in the average score of the pretest and post test. From the calculation results is known that the average post test score is higher than the average pretest score of 35.55> 23.1. Then it can be interpreted that traditional game â€œengklekâ€ is effective to students liveliness studying.